Permainan Imajinatif Berdasarkan Metakognisi dalam Belajar Matematika - Murti, Heru Astikasari Setya; Hastjarjo, Thomas Dicky (Gadjah Mada Journal of Psychology, 2015)
This research tried to investigate the effect of imaginative play in metacognition of math among children with intelligence as the covariable. Method used in this study was quasi experiment using the untreated controlled group design with dependent pretest and posttest samples. There were three groups used in this study, which were: Experiment Group 1, this group was given storytelling as the treatment, Experiment Group 2, this group was given pretending plays as the treatment, and Group 3 is a control group. Metacognition was measured with Metacognitive Skills and Knowledge Assessment developed by Desoete, Roeyers, & Buysse (2001), meanwhile intelligence was measured with Standard Progressive Matrices developed by Raven. Using the statistic of ancova, the result showed the value of F 12.526 (p<0.05) meaning that by controlling intelligence, it was found that there was an effect of imaginative play to metacognition. Based on pairwise comparison it was found that: a) there was a significant difference of metacognition between the group 1 (storytelling as the treatment) and group 3 (control group), b) there was a significant difference of metacognition between the group 1 (storytelling as the treatment) and group 2 (pretending play as the treatment), but 3) there was no significant difference of metacognition between the group 2 (pretending play as the treatment and group 3 (control group). It was found that the effective contribution of imaginative play to the variance of metacognition was 29.5% (R squared=0.295) and effective contribution of intelligence to the variance of metacognition was 10.7% (R squared= 0.107).Keywords: imaginative play, storytelling, pretending play, metacognition